HARUSKAH PEMBANGUNAN BERHENTI DILAKUKAN? - Huruta, Andrian Dolfriandra (KRITIS, 2016)
This article aims to describe some efforts of every country  worldwide to promote welfare of the society like economic, social, environment aspects without harming the environment or social life. There is an effort to support development thought some great event such as the UN conference on sustainable development (Rio+20). This effort creates millennium development goals and sustainable development goals. However this effort still creates some problems such as ecological, social conflict, inequality, security, poverty and etc. So that there are some action that we can do to reduce some problems such as increase the role of global citizen, development ethics and wisdom.Kata kunci:  Pembangunan, Etika Pembangunan, Masyarakat Global, Kearifan